Identification of the critical depth-of-cut through a 2D image of the cutting region resulting from taper cutting of brittle materials. (27th March 2018) - Gu, Wen; Zhu, Zhiwei; Zhu, Wu-Le; Lu, Leyao; To, Suet; Xiao, Gaobo
Abstract: An automatic identification method for obtaining the critical depth-of-cut (DoC) of brittle materials with nanometric accuracy and sub-nanometric uncertainty is proposed in this paper. With this method, a two-dimensional (2D) microscopic image of the taper cutting region is captured and further processed by image analysis to extract the margin of generated micro-cracks in the imaging plane. Meanwhile, an analytical model is formulated to describe the theoretical curve of the projected cutting points on the imaging plane with respect to a specified DoC during the whole cutting process. By adopting differential evolution algorithm-based minimization, the critical DoC can be identified by minimizing the deviation between the extracted margin and the theoretical curve. The proposed method is demonstrated through both numerical simulation and experimental analysis. Compared with conventional 2D- and 3D-microscopic-image-based methods, determination of the critical DoC in this study uses the envelope profile rather than the onset point of the generated cracks, providing a more objective approach with smaller uncertainty.